2009
DOI: 10.4103/0250-474x.58186
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of quercetin in the regression of ethanol-induced hepatotoxicity

Abstract: This study examined the protective effects of quercetin on chronic ethanol-induced liver injury. Rats were treated with ethanol at a dose of 4 g/100 g/day for 90 days. After ethanol intoxication, levels of serum amino transferases were significantly elevated. Decreased activity of superoxide dismutase, catalase, glutathione peroxidase and glutathione reductase was also observed on ethanol administration. Increased amounts of lipid peroxidation products viz. hydroperoxides, conjugated dienes and malodialdehyde … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 23 publications
0
8
1
Order By: Relevance
“…Ethanol may increase the activity of liver enzymes in mature organisms [50][51][52], but in the present study, the lowest activity was found in the group of animals receiving beer compared with the other groups. Therefore, it may be assumed that any component of beer may have simultaneously influenced the level of protein carbonyl groups and the activity of ALT in the liver of growing rats, but this should be confirmed by further studies.…”
Section: Discussioncontrasting
confidence: 65%
“…Ethanol may increase the activity of liver enzymes in mature organisms [50][51][52], but in the present study, the lowest activity was found in the group of animals receiving beer compared with the other groups. Therefore, it may be assumed that any component of beer may have simultaneously influenced the level of protein carbonyl groups and the activity of ALT in the liver of growing rats, but this should be confirmed by further studies.…”
Section: Discussioncontrasting
confidence: 65%
“…Alcohol feeding causes elevation in serum activities of AST, ALT, ALP, γGT and LDH enzymes which are markers of liver damage. In the study reported by Vidhya et al (2009) ethanol treated group resulted in significant increase in AST and ALT activities, which is an indication of hepatocellular damage in rats, whereas treatment with quercetin reduced ethanol -induced toxicity as indicated by the lowering of marker enzymes. In alcohol intoxication as a result of structural changes, an increase in the cell membrane permeability to ions results.…”
Section: Discussionmentioning
confidence: 90%
“…A recent report suggested that genistein or apigenin pretreatment could strengthen hepatic antioxidant ability, which contributed to inhibiting the production of CYP2E1-mediated reactive oxygen species, then downregulating the oxidative stress, and finally attenuating alcoholic liver injury [ 13 , 21 ]. Likewise, quercetin and EGCG supplementation could improve the inhibited antioxidant enzyme activity or block the MDA contents in liver resulting from chronic alcohol intake [ 24 , 32 ]. Our data denoted that, although quercetin was more effective at enhancing the HO-1 level ( Figure 4 B), apigenin, naringenin, and genistein had a more efficient effect in terms of increasing the activities of SOD, CAT, GSH, and GSH-Px ( Figure 4 C–F), in agreement with former results.…”
Section: Discussionmentioning
confidence: 99%